Структура и математическая модель канала распространения и регистрации рентгеновского излучения - Кипенский, Андрей Владимирович; Хоменко, Е. В.; Литвиненко, С. В.; Романов, О. И.; Безгинова, О. Н. (Академия наук прикладной радиоэлектроники, 2017)
The mathematical model of the X-ray-opto-electronic channel is proposed, which reflects the physical processes of the image signals’ formation and recording and makes it possible to determine the energy characteristics of the X-ray system, such as the signal-to-noise ratio at the output of the position sensitive detector and its quantum efficiency at a given exposure dose and quality characteristics individual elements. The technique was developed with using the mathematical model of the channel for analyzing the energy characteristics of a detector based on charge-coupled devices when visualizing the inhomogeneity of a given X-ray contrast.
Keywords: рентгенографические системы; позиционно-чувствительный детектор; регистрация сигналов; математическая модель